Katoba Tradition as a Cultural Pedagogy of Repentance in Muna: A Catholic Theological Reading toward the Sacrament of Penance - Pella, Samuel; Hanta, Xalastinus Jasper; Evan Kaba, Geofrey Roderic (Litbang STFT Widya Sasana Malang, 2026)
This article interprets the Katoba Tradition in Muna culture as a cultural pedagogy of repentance and examines it from the perspective of Catholic theology, particularly in relation to the Sacrament of Penance. Rather than equating Katoba with the sacrament, this study argues that Katoba functions as a preparatory horizon that forms moral, awareness, responsibility, and openness to conversion. Using a qualitative literature-based approach supported by contextual insights, the article analyses the symbolic and ethical dimensions of Katoba in dialogue with Catholic understanding of repentance, reconciliation, and sacramental grace. Grounded in biblical theology and Church teaching, the study identifies both convergences and limits between Katoba and the Sacrament of Penance. While Katoba emphasizes moral purification and social harmony, the sacrament offers holistic reconciliation with God and the Church through Christ’s salvific grace. Employing Bevans’ synthesis and countercultural models, this article proposes an inculturative approach that respects Muna culture while safeguarding the theological uniqueness of the Sacrament of Penance.